2015
DOI: 10.1007/s11356-015-5196-x
|View full text |Cite
|
Sign up to set email alerts
|

Human and animal enteric virus in groundwater from deep wells, and recreational and network water

Abstract: This study was designed to assess the presence of human adenovirus (HAdV), rotavirus-A (RVA), hepatitis A virus (HAV), and porcine circovirus-2 (PCV2) in groundwater from deep wells, and recreational and network waters. The water samples were collected and concentrated and the virus genomes were assessed and quantified by quantitative PCR (qPCR). Infectious HAdV was evaluated in groundwater and network water samples by integrated cell culture using transcribed messenger RNA (mRNA) (ICC-RT-qPCR). In recreationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 37 publications
1
26
0
1
Order By: Relevance
“…Rotaviruses are the major cause of childhood diarrheal disease detected in different water environments worldwide, including groundwater [11,40], even though waterborne outbreaks have been only sporadically documented. In Italy, Rotaviruses are a major cause of hospitalization among pediatric-aged children in Apulia, especially in the Salento area [41].…”
Section: Discussionmentioning
confidence: 99%
“…Rotaviruses are the major cause of childhood diarrheal disease detected in different water environments worldwide, including groundwater [11,40], even though waterborne outbreaks have been only sporadically documented. In Italy, Rotaviruses are a major cause of hospitalization among pediatric-aged children in Apulia, especially in the Salento area [41].…”
Section: Discussionmentioning
confidence: 99%
“…We used the SYBR GREEN technique to detect and quantify our DNA product, because it is a simple, inexpensive and effective technique to detect both viruses in water [3]. We applied a method using a selected conservation region, namely, open reading frame 1 (ORF 1, part of the RdPd gene) in the case of NV, while a segment of gene 4 that codes for the outer capsid protein VP4, with an expected size of 345 bp, was selected for the case of RV.…”
Section: Discussionmentioning
confidence: 99%
“…Infectious agents can be spread in this way, particularly during periods of low flow [1,2]. Although the number of viral particles in the surface water is very low, ten viral particles are sufficient for a healthy individual to be infected [3,4]. …”
Section: Introductionmentioning
confidence: 99%
“…HAdVs carried by recreational waters have been reported in different regions of Brazil [28], [29], [30], [31], [32]. Vieira et al.…”
Section: Adenovirusesmentioning
confidence: 99%
“…In the state of Rio de Janeiro (southeastern Brazil), studies conducted at Olympic venues showed 25.3% and 93.1% of positive samples respectively for HAdV-F and HAdV-C [28]. Studies carried out in the Lagoa do Peri (Santa Catarina, in the south of the country) found all samples to be positive for HAdV [29]. In the state of Rio Grande do Sul (southern Brazil), studies in Lake Guaíba showed about 78% positive samples for AdV [30].…”
Section: Adenovirusesmentioning
confidence: 99%